Analysis Of The Mechanism For Making A Deed Of Sale And Purchase Of Land Rights Based On Power Of Attorney Selling Notarial - Frisila, Frili; Bhudiman, Budy; Lestari, Nisa (JURNAL MAHASISWA YUSTISI, 2023)
In obtaining the right to ownership of an object on a plot of land, one of them can be organized through buying and selling. As time goes by with various reasons and objectives, it is not uncommon in organizing everything related to the action of the law, then as a human being who is classified as a legal subject, of course, is not able to do so directly by himself. Related to the problems found in the occurrence of a transfer of ownership of rights to an object of land, in imposing a power of attorney in writing must be contained in an authentic deed which in the case of its making must be before a Notary. The legality of the power of attorney contained in the power of sale deed and the binding of the sale and purchase agreement as a form of an authentic deed whose validity can be guaranteed when viewed from the side of the agreement law which explains how the agreement can be said to be valid contained in Article 1320 of the Civil Code has been fulfilled. This research aims to analyze several issues to answer why it is still often found in making a deed of sale and purchase that the basis is a notarially legalized power of attorney to sell, and explain how the mechanism and legality of the validity of a notarially legalized power of attorney to sell deed when transferring a right.